Correlates of time spent walking and cycling to and from work: baseline results from the commuting and health in Cambridge study - Panter Jenna; Griffin Simon; Jones Andrew; Mackett Roger; Ogilvie David (BMC, 2011)
Abstract Purpose Environmental perceptions and psychological measures appear to be associated with walking and cycling behaviour; however, their influence is still unclear. We assessed these associations using baseline data from a quasi-experimental cohort study of the effects of major transport infrastructural developments in Cambridge, UK. Methods Postal surveys were sent to adults who travel to work in Cambridge (n = 1582). Questions asked about travel modes and time spent travelling to and from work in the last week, perceptions of the route, psychological measures regarding car use and socio-demographic characteristics. Participants were classified into one of two categories according to time spent walking for commuting ('no walking' or 'some walking') and one of three categories for cycling ('no cycling', '1-149 min/wk' and ' ≥ 150 min/wk'). Results Of the 1164 respondents (68% female, mean (SD) age: 42.3 (11.4) years) 30% reported any walking and 53% reported any cycling to or from work. In multiple regression models, short distance to work and not having access to a car showed strong positive associations with both walking and cycling. Furthermore, those who reported that it was pleasant to walk were more likely to walk to or from work (OR = 4.18, 95% CI 3.02 to 5.78) and those who reported that it was convenient to cycle on the route between home and work were more likely to do so (1-149 min/wk: OR = 4.60, 95% CI 2.88 to 7.34; ≥ 150 min/wk: OR = 3.14, 95% CI 2.11 to 4.66). Positive attitudes in favour of car use were positively associated with time spent walking to or from work but negatively associated with cycling to or from work. Strong perceived behavioural control for car use was negatively associated with walking. Conclusions In this relatively affluent sample of commuters, a range of individual and household characteristics, perceptions of the route environment and psychological measures relating to car use were associated with walking or cycling to and from work. Taken together, these findings suggest that social and physical contexts of travel decision-making should be considered and that a range of influences may require to be addressed to bring about behaviour change.